EFFECTIVENESS OF THE MEDIATION PROCESS IN RESOLVING DIVORCE CASES AT THE DEPOK RELIGIOUS COURT - Basri, Rara Genta Munggarani; Malik, Ibnu; Sutisna, Sutisna; Hambari, Hambari (MIZAN: JOURNAL OF ISLAMIC LAW, 2024)
The issuance of the Supreme Court Regulation of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures indicates that the mediation process has received special attention by the Judiciary Institution because this process is a process that has a positive impact on the parties and is linear with the principles of the judiciary, namely fast, simple and low cost. Mediation is a way of resolving disputes through a negotiation process to obtain an agreement between the parties assisted by a mediator. This study used qualitative research methods. The type of research used is a case study, by taking a survey approach and conducting direct observations as well as conducting interviews with mediators and litigants. The research consists of field studies and literature studies (Field Research and Library Research). The Depok Religious Court has carried out the Mediation Process in accordance with the rules Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Courts. The mediation process at the Depok Class 1 A Religious Court in accordance with PERMA No.1 of 2016 is still not effective with a success rate of only achieved about 2% Success with the issuance of a peace certificate, 8% Success by revoking the divorce case and 23% succeeded in peace but still choose Divorce.